A riped jackfruit (Arthocarpus heterophyllus Lamk.) is one of the most popular fruit among tropical fruits, but it has inferior characteristic such as perishable, time consumed to served in fresh condition for peeling, and it consists of something sticky. Therefore a minimal processing must be done. This study is aimed to evaluate the respiration rate and find out the optimum condition for lengthening the storage life of minimally processed jackfruit under a modified atmospheric packaging. Accor - Ni Made Sudiari; Sutrisno . (Jurnal Keteknikan Pertanian, 1998)
A riped jackfruit (Arthocarpus heterophyllus Lamk.) is one of the most popular fruit among tropical fruits, but it has inferior characteristic such as perishable, time consumed to served in fresh condition for peeling, and it consists of something sticky. Therefore a minimal processing must be done. This study is aimed to evaluate the respiration rate and find out the optimum condition for lengthening the storage life of minimally processed jackfruit under a modified atmospheric packaging. According to its respiration pattern, a jackfruit is classified as a climacteric fruit, due to its sudden increase of evaluated C02. The optimum gas composition for MAP is 4-7% 02 and 10-12% C02 with a storage temperature of 5 'C. The MAP of jackfruit using Styrofoam tray and Stretch Film packaging is able to lengthen its storage until 8 days.